Is administration of anti-MRSA drugs recommended for patients with pneumonia when MRSA is isolated from respiratory specimens? A systematic review and meta-analysis - Fujikura, Yuji; Ohno, Tomohiro; Seki, Masafumi; Mitsutake, Kotaro (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2024)
It is unclear whether anti-methicillin-resistant Staphylococcus aureus (MRSA) drugs should be uniformly administered to patients with pneumonia when MRSA is isolated from respiratory specimens. A systematic review was conducted to evaluate the efficacy of the uniform administration of anti-MRSA drugs. Two researchers independently searched the literature as of December 2022, extracted relevant papers, and performed a meta-analysis. The outcomes were mortality and adverse events. No applicable randomized controlled trials were found during the study period, but four observational studies were extracted. The relative risk of mortality in the anti-MRSA group was 1.67 [95% confidence interval 0.65-4.30], which did not differ significantly from the non-administered group. Further investigation into the background of patients demonstrated that anti-MRSA drugs were administered to groups in which only MRSA was cultured. However, the pneumonia severity index did not differ from that in the non-treated group. No studies of adverse events were found. Our review did not find a beneficial contribution to mortality from uniform anti-MRSA medication to patients with pneumonia when MRSA was isolated from respiratory specimens. Factors determining risk-based individualized treatment should be validated as the future question.It is unclear whether anti-methicillin-resistant Staphylococcus aureus (MRSA) drugs should be uniformly administered to patients with pneumonia when MRSA is isolated from respiratory specimens. A systematic review was conducted to evaluate the efficacy of the uniform administration of anti-MRSA drugs. Two researchers independently searched the literature as of December 2022, extracted relevant papers, and performed a meta-analysis. The outcomes were mortality and adverse events. No applicable randomized controlled trials were found during the study period, but four observational studies were extracted. The relative risk of mortality in the anti-MRSA group was 1.67 [95% confidence interval 0.65-4.30], which did not differ significantly from the non-administered group. Further investigation into the background of patients demonstrated that anti-MRSA drugs were administered to groups in which only MRSA was cultured. However, the pneumonia severity index did not differ from that in the non-treated group. No studies of adverse events were found. Our review did not find a beneficial contribution to mortality from uniform anti-MRSA medication to patients with pneumonia when MRSA was isolated from respiratory specimens. Factors determining risk-based individualized treatment should be validated as the future question.